Synthesis of a Novel Hydrogel composite Based on CMC-g-poly(AA-co-IA)/Montmorrolonite - Sadeghi, Mohammad; Soleimani, Fatemeh (Asian Journal of Chemistry, 2012)
In this work, A novel superabsorbent hydrogel composite based on carboxymethylcelloluse have been prepared via graft copolymerization of acrylamide and itaconic acid monomers in the presence of montmorolonite powder as a clay and methylenebisacrylamide as a crosslinking agent and ceric ammonium nitrate as an initiator. A mechanism for the superabsorbent hydrogel formation was also suggested. Hydrogel formation was confirmed by FTIR spectroscopy. Results from scanning electron microscopy observation also showed a porous structure with smooth surface morphology of the hydrogel. Furthermore, the water absorbency of hydrogels composite was measured in solutions with pH ranged 1 to 13.